Eulerian dynamics of a bicone. (5th August 2014) - Decuyper, M.
The purpose of this paper is to resume the problem of wheelset dynamics at a quite fundamental level, by deriving the Eulerian equations of motion of an idealized model of wheelset, on an idealized track. In fact, the translation and rotation equations are derived for a bicone (pair of conical wheels) of any conicity on a straight sharp–edged track. The kinematical constraints are deduced from nonlinear analytical principles, which are then linearized. For the contact forces, a model inspired from Kalker's creep model has been chosen which was adapted to separate somewhat the influence factors, in view of parametric stability studies. The equations are linearized around a nominal uniform motion without any slip; equations of lateral motion are isolated and given a non–dimensional matrix form. They are then compared to equations presented by other authors.